A vibrational spectroscopy study on 3-aminophenylacetic acid by DFT calculations - Akkaya, Yasemin; Balcı, Kubilay; Gören, Yeliz; AKYÜZ, SEVİM (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2015)
In this study, in which the group vibrations of 3-aminophenylacetic acid were investigated by electronic structure calculations based on Density Functional Theory (DFT), the possible stable conformers of the molecule were searched through a relaxed "potential energy surface scan" carried out at B3LYP/6-31G(d) level of theory. The corresponding equilibrium geometrical and vibrational spectral data for each of the determined stable conformers and for their ipossible dimer structures were obtained through "geometry optimisation" and "frequency" calculations carried out at B3LYP/6-31G(d) and B3LYP/6-311G++(d,p) levels of theory. The obtained results confirmed that anharmonic wavenumbers calculated at B3LYP/6-311G++(d,p) level generally quite well agree with the experimental wavenumbers, however, harmonic wavenumbers calculated at both levels of theory need an efficient refinement for a satisfactory agreement with experiment. In particular, the harmonic wavenumbers, IR and Raman intensities refined within Scaled Quantum Mechanical Force Field (SQM FF) methodology constituted the primary data set in the interpretatiori of the experimental FT-IR, FT-Raman and dispersive Raman spectra of 3-aminophenylacetic acid. By the help of these refined spectral data, the effects of conformation and intermolecular hydrogen bonding on the fundamental bands observed in the experimental spectra could be correctly predicted. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aminophenylacetic acid; Vibrational spectra; Hydrogen bonding; SQM FF methodology; Dual scale factors; Scaled frequencies; Density-Functional Theory; Force-Fields; Scaling Factors; Raman-Spectra; Benzoic-Acid; Molecular Geometries; Phenylacetic Acid; Benzene Molecule; Infrared-Spectra; Hartree-Fock